Editorial - Padaria, R N (Indian Journal of Extension Education, 2020)
It is really disheartening to note that India ranks 94th out of the 107 countries inÂ Global Hunger Index-2020. That India is home to 46.6 million stunted children, a third of world’s total as per Global Nutrition Report 2018, has been a matter of great concern. Malnutrition is a global challenge and any country cannot aim to attain economic and social development goals without addressing the issue of malnutrition. The Honourable Prime Minister Narendra Modi has pledged for malnourished free India or malnutrition free India and has exhorted every citizen to help achieve thisÂ goal. To provide impetus to nutrition drive, the government has decided to mark September as "POSHAN" (nutrition) month with the goal of improving the nutritionalÂ status of children up to 6 years old, pregnant women and lactating mothers. There is need to devise extension strategies for ensuring household nutritional security.Â Besides promotion of bio-fortified varieties of crops, it is essential to build capacities of rural women through awareness, skill development, and augmenting institutional arrangements for promotion of kitchen gardens and terrace gardens forÂ vegetableÂ production at household level, community nutri-gardens, integrated farming system, processing and value addition, and dietary diversification.Â I extend my sincere thanks to all the authors for making valuable contributions. IÂ also extend sincere thanks to all the expert members in the editorial board. Special thanks are extended to Dr. M.S.Nain and Dr. Himanshu De for their painstakingÂ efforts.Â Special thanks are extended to the President, ISEE; Dr US Gautam for providing insightful thoughts and guidance in bring out this issue. Dr. Bhanu Mishra deserves special thanks for making committed efforts inÂ compiling and thorough editing of the papers. (Rabindra Nath Padaria)